2019
DOI: 10.1111/bjh.16260
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of CD4+PD‐1+HLA‐DR+ T cells is associated with disease progression in CLL

Abstract: Summary Chronic lymphocytic leukaemia (CLL) patients often have abnormal expansions of CD4+ and CD8+ T cells and this can be associated with progressive disease. To characterise the key T‐cell populations involved in this phenomenon, we used flow cytometry and 11 phenotypic markers to study 74 CLL patients and 14 controls. T cells of CLL patients were more phenotypically complex than those of healthy controls with significant increases in the frequencies of CD4 and CD8 memory T cells expressing exhaustion‐, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Interestingly, we observed that the proportion of the T and NKT cell compartment was increased in CLL patients (Figure 2d), as were circulating stem cells (as identified by CD34+ expression), especially closer to treatment (Figure 2e), suggesting marrow stress with higher disease burden. In keeping with previously published data [14][15][16] , we saw a decrease in naive CD8+ T cells, with corresponding increase in the CD8+ TEMRA population when comparing close-to-treatment CLL samples to HDs (Supplementary Figure 3). The use of HLA-DR in the staining further identified groups of CD8+ and CD4+ effector memory T cells that increased between CLL time point 1 and 2 with the CD4+ cluster being specifically enriched for PD-1 (Figure 2f-g and Supplementary Figure 3), similar to that reported by Elston et al (2020) 15 .…”
Section: Cycombine Enables Large-scale Integration Of Multi-batch Multi-panel Cytometry Datasupporting
confidence: 91%
“…Interestingly, we observed that the proportion of the T and NKT cell compartment was increased in CLL patients (Figure 2d), as were circulating stem cells (as identified by CD34+ expression), especially closer to treatment (Figure 2e), suggesting marrow stress with higher disease burden. In keeping with previously published data [14][15][16] , we saw a decrease in naive CD8+ T cells, with corresponding increase in the CD8+ TEMRA population when comparing close-to-treatment CLL samples to HDs (Supplementary Figure 3). The use of HLA-DR in the staining further identified groups of CD8+ and CD4+ effector memory T cells that increased between CLL time point 1 and 2 with the CD4+ cluster being specifically enriched for PD-1 (Figure 2f-g and Supplementary Figure 3), similar to that reported by Elston et al (2020) 15 .…”
Section: Cycombine Enables Large-scale Integration Of Multi-batch Multi-panel Cytometry Datasupporting
confidence: 91%
“…T H 2-polarized CD4 + T cells secrete cytokines that can limit CTL differentiation and proliferation such as IL-10 and IL-4, while CD4 + T Regs (FOXP3 + ) have significant immunosuppressive functions through various mechanisms and their pro-tumor role has been described in both solid tumors and lymphomas (13,(27)(28)(29). In CLL, in vitro and xenograft murine models have demonstrated a pro-tumor effect of the CD4 + T cell compartment in patients, with correlations of CD4 + subset counts and clinical outcome supporting this role (28,30). However, research using Eµ-TCL1-based murine models has suggested a more complex role of CD4 + T cells with some studies showing an anti-tumor function (31), while others demonstrating a dispensable role (23).…”
Section: T Cells and Anti-tumor Immunitymentioning
confidence: 99%
“…T cells from CLL patients have a higher expression of both the intracellular and surface forms of CTLA-4 compared to healthy controls (85,112). In addition, the upregulation of PD-1 was observed in CD4+ and CD8+ T cells from patients with CLL and was reported to associate with adverse prognosis (82,85,89,113). PD-1 expression is further increased in T cells from the lymphnode compared to the peripheral blood compartment (90,114).…”
Section: Phenotypic and Functional T-cell Alterationsmentioning
confidence: 99%